The Role of Culture, Leader Motivating Language, and Procedural Justice Climate on Organizational Identification - Fathiyah Faiha Faisal; Alice Salendu (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Emotional culture is a crucial aspect that can enhance organizational outcomes. However, research on affective aspects in the workplace is still underexplored and requires further investigation. This study aims to examine the moderating role of procedural justice climate in the relationship between leader motivating language and organizational identification, mediated by positive emotional culture. The study involved 158 employees with a minimum of one year of work experience and has a superior in their workplace. Measurement tools included the leader motivating language scale (α = 0.95), organizational identification scale (α = 0.74), positive emotional culture scale (α = 0.94), and procedural justice climate scale (α = 0.88), adapted into the Indonesian language. Data was analyzed with PROCESS model 4 and 14 by Hayes. The results indicate that 1) positive emotional culture partially mediates the relationship between leader motivating language and organizational identification; 2) procedural justice climate does not moderate the relationship between leader motivating language and organizational identification mediated by positive emotional culture. This study lays the groundwork for further research, suggesting that organizations should focus on organizatinal culture, therefore it increases employee’s organizational identification.